Impact of different sequences of mechanical and thermal processing on the rheological properties of Porphyridium cruentum and Chlorella vulgaris as functional food ingredients. Issue 4 (10th April 2018) - Bernaerts, Tom M. M.; Panozzo, Agnese; Verhaegen, Katrien A. F.; Gheysen, Lore; Foubert, Imogen; Moldenaers, Paula; Hendrickx, Marc E.; Van Loey, Ann M.
Abstract : Different processing sequences result in specific rheological properties of these microalgae as functional food ingredients. Abstract : Microalgae are a promising and sustainable source for enhancing the nutritional value of food products. Moreover, incorporation of the total biomass might contribute to the structural properties of the enriched food product. Our previous study demonstrated the potential of Porphyridium cruentum and Chlorella vulgaris as multifunctional food ingredients, as they displayed interesting rheological properties after applying a specific combination of mechanical and thermal processing. The aim of the current study was to investigate the impact of a different sequence of high pressure homogenization (HPH) and thermal processing on the thickening and gelling potential of these microalgal biomasses in aqueous suspensions. Thermal processing largely increased the gel strength and viscosity of both microalgae, which was ascribed to larger and stronger aggregates as a result of partial solubilization of polymers, while subsequent HPH generally reduced the rheological properties. Interestingly, large amounts of intact cells were still observed for both microalgae when HPH was performed after a thermal treatment, irrespective of the applied homogenization pressure, implying that cell disruption was hindered by the preceding thermal treatment. Although thermal processing was regarded as the most effective processing technique to obtain increased rheological properties, the combination with a preceding HPH treatment should still be considered when cell disruption is desired, for instance to increase the bioavailability of intracellular components. Finally, biomass of P. cruentum showed the largest potential for use as a structuring agent, as the gel strength and viscosity in thermally treated suspensions of this microalga were about 10 times higher than for C. vulgaris .